Manfaat Penggunaan Informasi Akuntansi Bagi Usaha Kecil dan Menengah (UKM) di Kota Padang - Arya Febriadi; Syamwil Syamwil; Efni Cerya (Jurnal Ecogen, 2019)
The contribution of Small Medium Enterprises (SMEs) is very important in supporting the growth of the Indonesian economy. In the continuity of the business, surely good management is needed. Management should be able to prepare financial statements so the accounting information that contained within it can be beneficial to the business. This study aims to determine the benefits of accounting information for Small and Medium Enterprises (SMEs) in Padang city. This type of research is descriptive qualitative. Data collection was carried out by interviews with informants using guidelines for interviews and documentation. The informants in this study are three small and medium enterprises (SMEs) that already preparing financial statements consisting of statements of financial position and income statements. The results of the study showed that accounting information beneficial for SMEs assisting in decision making process and accountability. Keyword: acounting information, small medium enterprises (smes), financial statement